2018
DOI: 10.5562/cca3356
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Amidohydrolases – From Structure to Function: Revisited

Abstract: The control of plant growth and development is a well-coordinated process between exogenous and endogenous signals. Auxins are plant hormones belonging to the endogenous signals, which control a vast array of different processes. While auxins are growth promoting at low concentrations, higher levels are often inhibitory. Therefore, the tight control of auxin concentrations in a given plant tissue is essential. Among several processes that participate in auxin homeostasis, we focused herein on the process of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…While the GH3 proteins of P. patens are similar in sequence and function to the higher plant enzymes [ 15 ], the hydrolysis pathway was thought not to take place at all, since the typical plant sequences for conjugate hydrolases were missing [ 75 ]. However, recent work provided experimental evidence for the possible hydrolysis of IAA amino acid conjugates in P. patens as well, since it was found that the moss contained sequences similar to bacterial auxin amidohydrolases [ 24 , 76 ] and its capacity to cleave some conjugates in vivo and in vitro [ 24 ]. These sequences were possibly acquired by horizontal gene transfer [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While the GH3 proteins of P. patens are similar in sequence and function to the higher plant enzymes [ 15 ], the hydrolysis pathway was thought not to take place at all, since the typical plant sequences for conjugate hydrolases were missing [ 75 ]. However, recent work provided experimental evidence for the possible hydrolysis of IAA amino acid conjugates in P. patens as well, since it was found that the moss contained sequences similar to bacterial auxin amidohydrolases [ 24 , 76 ] and its capacity to cleave some conjugates in vivo and in vitro [ 24 ]. These sequences were possibly acquired by horizontal gene transfer [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent work provided experimental evidence for the possible hydrolysis of IAA amino acid conjugates in P. patens as well, since it was found that the moss contained sequences similar to bacterial auxin amidohydrolases [ 24 , 76 ] and its capacity to cleave some conjugates in vivo and in vitro [ 24 ]. These sequences were possibly acquired by horizontal gene transfer [ 76 ]. Modeling of one protein sequence showed similarity to the respective proteins from A. thaliana [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Auxin metabolism and homeostasis have been extensively studied and numerous genes have been identified to date. A review of auxin homeostasis has been updated [ 7 , 8 , 9 , 10 , 11 , 12 ] and is summarized in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%